2006
DOI: 10.1016/j.phytochem.2005.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxonomy of Veroniceae and its allies in the Plantaginaceae

Abstract: In a chemosystematic investigation of tribe Veroniceae (Plantaginaceae), representatives of Camptoloma, Sibthorpia, Veronica subg. Pentasepalae and subg. Hebe, Veronicastrum, Wulfenia, and the related Ellisiophyllum and Globularia were examined for non-flavonoid glycosides. From the 14 species studied, 28 different iridoid glucosides and 10 caffeoyl phenylethanoid glucosides (CPGs), as well as salidroside and arbutin were isolated and characterized by NMR; of these, five compounds were previously unknown. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
58
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 71 publications
11
58
1
Order By: Relevance
“…Other studies have also confirmed the utilization of PhGs as taxonomic markers of genus Orobanche [142], Sibthorpia, and Ellisiophyllum (Plantaginaceae) [143]. Findings in chemotaxonomy based on PhGs are expected to provide a valuable measure for chemists to source rare PhGs from related species or genera.…”
Section: Chemotaxonomymentioning
confidence: 81%
“…Other studies have also confirmed the utilization of PhGs as taxonomic markers of genus Orobanche [142], Sibthorpia, and Ellisiophyllum (Plantaginaceae) [143]. Findings in chemotaxonomy based on PhGs are expected to provide a valuable measure for chemists to source rare PhGs from related species or genera.…”
Section: Chemotaxonomymentioning
confidence: 81%
“…16 or 11), since they apparently always occur together with these. Previously, the parent asystasioside E (17) has been found in the related Wulfenia baldaccii Degen together with its 6-O-cinnamoylester (Taskova et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The isolated compounds were identified by their 1 H and 13 C NMR spectra by comparison with spectra of known standards (Taskova et al, 2006). Dry leaf material (7 to 11 g) was extracted by blending in EtOH (50 ml).…”
Section: Phytochemical Analysismentioning
confidence: 99%